Факторы влияния на смысловые отношения в предложениях русского языка - Бак, Х. (Філологічний дискурс, 2017)
В статье рассмотрены теоретические положения соотношения
структуры языковых единиц и их смысловых отношений как объект изучения структурно-семантического направления современного
русского языка. Современные исследователи приводят доказательства, что лексика и синтаксис, представляя разные
уровни языковой системы, тесно связаны между собой: лексикой определяется как семантика синтаксических единиц, так и их
строение. При построении синтаксических единиц выбор лексики определяется потребностью говорящего дать ту или иную
информацию о действительности. Лексика активно вторгается в область синтаксических значений. Коммуникативный аспект
оказывает влияние на объем членов предложения, на смысловое разграничение подлежащего и сказуемого, усиливает или ослабевает
значение номинации. Эмоционально-оценочные элементы включают стилистический аспект и влияют на структуру предложения,
объединяя факторы семантические и грамматические. Направление семантического синтаксиса выдвинуло понятие пропозиции как
модели называемого предложением «положения дел». Структуру пропозиции определяет предикат, он указывает на участников
«положения дел» (актантов), определяет их количество и роли. Изучение смысловой организации предложения и факторов, влияющих
на их изменения, ведется одновременно со стороны лексикологии и семантического синтаксиса. Ключевым является положение о том,
что предложение, подобно слову, является номинативной единицей. Разница только в изображении корелятивной операции,
производимой субъектом. Фактор переходности синтаксических явлений – это параллельные взаимодополняющие функции. У статті розглянуто теоретичні положення співвідношення структури
мовних одиниць і їх смислових відносин як об’єкту вивчення структурно-
семантичного напряму сучасної російської мови. Сучасні дослідники доводять,
що лексика і синтаксис, представляючи різні рівні мовної системи, тісно пов’язані між собою: лексика визначає як семантику синтаксичних одиниць, так і їх будову. При будові синтаксичних одиниць вибір лексики визначається
потребою мовця дати ту чи іншу інформацію про дійсність. Лексика активно втручається в область синтаксичних значень. Комунікативний
аспект впливає на обсяг членів речення, на смислове розмежування підмета й
присудка, підсилює або послаблює значення номінації. Емоційно-оцінні елементи включають стилістичний аспект і впливають на структуру
речення, поєднуючи фактори семантичні й граматичні. Напрям семантичного синтаксису висунув поняття пропозиції як моделі названого
реченням «стану справ». Структуру пропозиції визначає предикат, він вказує
на учасників «стану справ» (актантів), визначає їх кількість і ролі. Вивчення
смислової організації речення і факторів, які впливають на їх зміни, ведеться
одночасно з боку лексикології й семантичного синтаксису. Ключовим є
положення про те, що речення, подібно до слова, є номінативною одиницею. Різниця тільки в зображенні корелятивної операції, виробленої суб’єктом. Фактор перехідності синтаксичних явищ – це паралельні взаємодоповнюючі функції. Introduction. The theoretical positions of the correlation of the structure of
linguistic units and their semantic relations as an object of studying the structural
and semantic direction of the modern Russian language are considered in the
article. Purpose. Investigate particular factors that affect the change in the
meaning relations in simple and complex sentences, depending on the lexical content
associated with the speech goal of a speaker or a writer. Methods.Descriptive,
analytical, comparative methods are used in the article. Results. Modern
researchers produce testimony to statement that the lexis and syntax, representing
different levels of the linguistic system, are closely related: vocabulary is defined as
the semantics of syntactical units, as their structure. In the construction of the
syntactic units, the choice of lexis is determined by the speaker’s needs to represent
this or that information about reality. Lexis invades actively the area of the syntactic
meanings. The communicative aspect influences the capacity of the members of
sentence, on the semantic discrimination of the subject and the predicate,
strengthens or weakens the value of the nominative meanings. Emotional-evaluative
elements include a stylistic aspect and affect the structure of the sentence, combining
semantic and grammatical factors. The direction of the semantic syntax put forward
the concept of proposition as a model called the sentence of the «state of affairs.» The
structure of the proposition is determined by the predicate, it indicates the
participants of the «state of affairs» (actants), determines their quantity and roles.
The study of the semantic organization of the sentence and the factors that influence
their changes is carried out simultaneously from the side of lexicology and semantic
syntax. The dominant is the proposition that a sentence, like a word, is a nominative
unit. The difference is only in the representation of the correlative operation
performed by the subject. The factor of the transitivity of syntactic phenomena is
parallel complementary functions. Conclusions. Understanding the community of
the words and sentences functions as nominative units combined the possibilities of
lexicology and syntax, which expanded the field of interpretation characteristics of
structural schemes of the sentence. Investigating the phenomenon of the transition of
the one type of syntactic unit to another, we indicated the general and complementary factors of the semantic relationship changings.